Prevalence and Determinant of Depression among Multi-Drug Resistance Tuberculosis: Study in Dr. Kariadi General Hospital - Mahalul Azam; Arulita Ika Fibriana; Fitri Indrawati; Indah Septiani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrouds: Multi-drug resistance tuberculosis (MDR-TB) adds the burden of tuberculosis (TB). Depression is a common comorbidity in TB patients. Prevalence of depression among MDR-TB patients was higher, i.e. 11-70%. Prevalence of depression among TB patients in Dr. Kariadi General Hospital was 51.9%. Previous study reported the determinants related to the depression in MDR-TB patients. This study explored the prevalence of depression in MDR-TB patients and its determinants. Methods: This study was a cross-sectional study conducted from July-August 2019. Data consisted of primary and secondary data from Dr. Kariadi General Hospital patients. Sample in this study involved 72 respondents, over 16 years old from 151 registered MDR-TB patients. Depression status was determined using Depression Anxiety Stress Scales obtained from the medical record. Subjects’ characteristics and determinants were collected from primary as well as secondary data. Descriptive data were presented in proportion. Chi-square test continued by Binary logistic regression was performed to determine the association between depression status and its determinants. A P-value